Use of the determined properties of a roughness of a surface in measurement of a geometrical form of object - Dzubenko, M.I.; Kolpakov, S.N.; Popov, I.V.; Pryyomko, A.A. (Физическая инженерия поверхности, 2013)
Classification of surfaces as roughness is carried out. The roughness can have the determined, stochastic or chaotic character, depending on a method of their forming. In the work the problem of finding of normal vector to a surface and coordinates of a point of lighting by a laser beam for the case of approximation of a roughness by a flat reflective diffraction grating is solved. Keywords: surface, roughness, diffraction grating, coherent radiation.